Sensory and Microstructural Properties of Cakes Made with Flour from Low Postharvest Physiologically Deteriorated Cassava - Alimi, J. P.; Ahemen, S. A.; Alimi, J. O.; Ajisafe, S. S.; Oke, O. A. (Journal of Food Industry, 2024)
The pertinent information generated from studying quality characteristics such as the structure and crumb properties of baked food products such as bread, cake etc. is very critical as it enhances product quality and inevitably help improve consumer acceptability. This research was carried out to assess the sensory qualities and investigate the microstructural properties of cakes made with high quality cassava flour (HQCF) from selected varieties of low postharvest physiologically deteriorated (PPD) cassava. Wholesome four varieties of yellow-fleshed Low PPD cassava and one variety of high PPD cassava were processed into high quality cassava flour flowing unit operations such peeling, washing, grating, pressing, pulverization and eventual drying using flash dryer operated at 120 °C for 10 minutes followed by milling with cyclone hammer mill fitted with a screen of 250 µm aperture size; the HQCF was allowed to cool, sieved and then packed into high density polyethylene bag. The cakes were analyzed for sensory and microstructural properties. Analysis of variance was performed on the data generated while significant means were separated applying Duncan Multiple Range Test using Statistical Package for Social Sciences (SPSS version 25.0). Generally, there was no significant difference (p≥0.05) in the sensory qualities (Color, texture, aroma, taste, flavor and overall acceptability) of the cakes made. The cake samples had sensory scores with ranges: (2.20 – 3.40), texture (2.60 – 4.10), aroma (2.90 – 4.20), taste (3.10 – 3.80) favor (2.90 – 3.80) and overall acceptability (2.90 – 3.70). The most preferred cake sample was C-070593 (cake sample baked with HQCF from IITA-TMS-IBA070593 cassava. Microstructural properties of cake baked with wheat flour was significantly different from cakes baked with HQCF from low PPD cassava owing to water absorption capacity, starch gelatinization characteristics and dough composition such as gluten quality. Cakes of acceptable sensorial and microstructural characteristics similar to that made with 100% wheat flour were produced with HQCF from selected varieties of low PPD cassava.